(untitled) (Annals of Medical Research, 2021)
Aim: Irisin is a newly identified myokine that is released from skeletal muscles after exercise and has a regulatory role on energy metabolism. Low serum irisin causes glucose metabolism disorder and metabolic syndrome. The aim of this study was to assess neonatal irisin levels in infants born to mothers with and without gestational diabetes mellitus (GDM).Material and Methods: Hundred neonates born at gestational ages of 26-40 weeks were included in the study. Neonates born to mothers with GDM comprised one group; neonates born to mothers without GDM were evaluated in three groups: appropriate for gestational age (AGA), small for gestational age (SGA), and large for gestational age (LGA) infants. Peripheral blood samples were obtained at postnatal 48 hours and analyzed for serum irisin levels by ELISA.Results: Serum irisin levels in infants born to GDM mothers were significantly lower (mean 0.81 ng/ml) than AGA newborns of healthy mothers (mean 1.21 ng/ml) (p=0.017). Serum irisin levels were not correlated with gestational age, birth weight, Z-score, or BMI (p>0.05). Conclusion: This study show that serum irisin levels are lower in infants born to GDM. Lower irisin levels in the neonatal period may increase the risk of obesity, metabolic syndrome, and glucose metabolism disorder later in life.Keywords: Irisin; newborn; gestational diabetes.